Exposure to Prenatal Stress Is Associated With an Excitatory/Inhibitory Imbalance in Rat Prefrontal Cortex and Amygdala and an Increased Risk for Emotional Dysregulation - Marchisella, Francesca; Creutzberg, Kerstin Camile; Begni, Veronica; Sanson, Alice; Wearick-Silva, Luis Eduardo; Tractenberg, Saulo Gantes; Orso, Rodrigo; Kestering-Ferreira, Érika; Grassi-Oliveira, Rodrigo; Riva, Marco Andrea (Frontiers in Cell and Developmental Biology, 2021)
Epidemiological studies have shown that environmental insults and maternal stress during pregnancy increase the risk of several psychiatric disorders in the offspring. Converging lines of evidence from humans, as well as, from rodent models suggest that prenatal stress (PNS) interferes with fetal development, ultimately determining changes in brain maturation and function that may lead to the onset of neuropsychiatric disorders. From a molecular standpoint, transcriptional alterations are thought to play a major role in this context and may contribute to the behavioral phenotype by shifting the expression of genes related to excitatory and inhibitory transmission balance (E/I). Nevertheless, the exact neurophysiological mechanisms underlying the enhanced vulnerability to psychopathology following PNS exposure are not well understood. In the present study, we used a model of maternal stress in rats to investigate the distal effects of PNS on the expression of genes related to glutamatergic and GABAergic neurotransmissions. We inspected two critical brain regions involved in emotion regulation, namely the prefrontal cortex (PFC) and the amygdala (AMY), which we show to correlate with the behavioral effects detected in adult rat offspring. We observed that PNS exposure promotes E/I imbalance in the PFC of adult males and females, by dysregulating the expression of glutamatergic-related genes. Moreover, we found that such an effect is more prominent in males and it is accompanied by increased expression of the Npas4 gene in PFC parvalbumin-positive interneurons (PV), suggesting an altered regulation of inhibitory synapse formation. In the AMY, PNS more evidently affects the transcription of GABAergic-related genes, shifting the balance toward inhibition. Furthermore, AMY E/I derangements correlated with anxiety-related responses in male PNS offspring. Collectively, our findings suggest that the E/I dysregulation.